Spatial calibration of large volume photogrammetry based metrology systems. (May 2015) - Summan, R.; Pierce, S.G.; Macleod, C.N.; Dobie, G.; Gears, T.; Lester, W.; Pritchett, P.; Smyth, P.
Highlights: Accuracy study of a Vicon T160 system using a Leica AT901 laser tracker. Error surface found to have a convex shape. Mean errors of 1.38 mm and 2.95 mm for different calibration artefacts. Scaling factor issue identified and estimated for the photogrammetry system. With scaling applied, mean errors reduce to 0.51 mm and 0.59 mm. Abstract: Photogrammetry systems are used extensively as volumetric measurement tools in a diverse range of applications including gait analysis, robotics and computer generated animation. For precision applications the spatial inaccuracies of these systems are of interest. In this paper, an experimental characterisation of a six camera Vicon T160 photogrammetry system using a high accuracy laser tracker is presented. The study was motivated by empirical observations of the accuracy of the photogrammetry system varying as a function of location within a measurement volume of approximately 100 m 3 . Error quantification was implemented through simultaneously tracking a target scanned through a sub-volume (27 m 3 ) using both systems. The position of the target was measured at each point of a grid in four planes at different heights. In addition, the effect of the use of passive and active calibration artefacts upon system accuracy was investigated. A convex surface was obtained when considering error as a function of position for a fixed height setting confirming the empirical observations when using either calibration artefact. Average errors of 1.48 mm and 3.95 mm were obtained for the active and passive calibration artefacts respectively. However, it was found that through estimating and applying an unknown scale factor relating measurements, the overall accuracy could be improved with average errors reducing to 0.51 mm and 0.59 mm for the active and passive datasets respectively. The precision in the measurements was found to be less than 10 μm for each axis.